Public sentiment of the population in the new social reality: a municipal cross-section - I. N. Dementieva (Вестник университета)
The article analyses the dynamics of public sentiment of residents of the Vologda Region. The author’s methodology for index analysis of public sentiment of the region, using the results of sociological monitoring, has been presented. At the same time, the main emphasis has been made on assessing the peculiarities of public sentiment of residents of municipalities – the cities of Vologda and Cherepovets in the context of changing social reality. The results of the study showed that the analysis of public sentiment in the monitoring regime makes it possible to obtain important information about the quality of state and municipal administration and determine the areas for improving their effectiveness, which is particularly relevant in the context of the socio-economic and epidemiological crisis.